ISLAM MODERAT DALAM PERDEBATAN - RAHMATULLAH RAHMATULLAH (Jurnal Dialog, 2017)
The term of “moderate”constitutes quite controversial term among Islamic scholars. Some Islamic scholars supported the trend of moderate Muslim, while others disagreed since the moderate term had negative effects on Muslim and Islam itself. Therefore, this article deals with the dispute of ‘moderate‘ term among scholars. Besides, the article also portrays some characteristics of Muslim moderate according to several contemporary Muslim scholars.‘Moderat’ merupakan istilah yang cukup kontroversial di kalangan sarjana Islam. Beberapa sarjana Islam mendukung trend Islam moderat, sementara yang lainnya tidak mendukung dengan alasan istilah moderat memiliki efek negatif terhadap muslim dan Islam sendiri. Oleh karena itu, artikel ini memaparkan perdebatan istilah ‘moderat’ di antara para sarjana muslim. Di samping itu, artikel ini juga memaparkan sejumlah karakteristik muslim moderat menurut sejumlah sajana muslim kontemporer.KEYWORDS: moderate, characteristic, movement, radical